Creation of an E-Commerce Website as a Media for Promoting Fish Skin Processing SME Products in the Malabero Village Fishermen Group, Bengkulu City - Febzi Fiona; Effed Darta Hadi; Rina Suthia Hayu (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The portrait of fishermen's life is often found in several coastal areas, where fishermen who borrow capital from middlemen, in addition to having to pay principal loans and interest, are also not allowed to sell their fish catches to the fish auction site (TPI), but must go to the middlemen at meager prices. Meanwhile, the middlemen sell it to the TPI at a very profitable market price. The fate of traditional fishermen in the hands of middlemen is of course complicated and hinders the fishermen's desire to control and develop their business and improve their welfare. To break the chain of problems of traditional fishermen, in the Malabero sub-district, Bengkulu City, the Malabero Fishermen's Group was formed with the hope of improving the welfare of its members. One of the efforts that have been made is to process fish skin into other more useful products. For example, fish crackers, souvenirs, and others. And this business has not been welcomed by consumers. One of the reasons is due to the lack of promotion from the producers. Producers, in this case, members of the fishing group, still market their products manually. By displaying their products and leaving them in stalls around their area. The development of information technology has now deeply penetrated all levels of society in Indonesia. Almost everyone uses cellphones, and smartphones and even actively uses the internet. The proliferation of smartphone users in this case the internet is certainly one of the opportunities for marketing products. Online sales such as Shopee, tokopedia, and Lazada show that public interest in online trading is very large.  From the partner's problem, an e-commerce website development training was held as a medium for promoting the production of the Malabero Fishermen Group.